Methylation of NRN1 is a novel synthetic lethal marker of PI3K‐Akt‐mTOR and ATR inhibitors in esophageal cancer. Issue 7 (16th May 2021) - Du, Wushuang; Gao, Aiai; Herman, James G.; Wang, Lidong; Zhang, Lirong; Jiao, Shunchang; Guo, Mingzhou
Abstract: Wnt, PI3K‐Akt‐mTOR, and NF‐κB pathways were reported to be involved in DNA damage repair (DDR). DDR‐deficient cancers become critically dependent on backup DNA repair pathways. Neuritin 1 (NRN1) is reported to be involved in PI3K‐Akt‐mTOR, and its role in DDR remains unclear. Methylation‐specific PCR, siRNA, flow cytometry, esophageal cancer cell lines, and xenograft mouse models were used to examine the role of NRN1 in esophageal cancer. The expression of NRN1 is frequently repressed by promoter region methylation in human esophageal cancer cells. NRN1 was methylated in 50.4% (510/1012) of primary esophageal cancer samples. NRN1 methylation is associated significantly with age ( P  < .001), tumor size ( P  < .01), TNM stage ( P  < .001), differentiation ( P  < .001) and alcohol consumption ( P  < .05). We found that NRN1 methylation is an independent prognostic factor for poor 5‐y overall survival ( P  < .001). NRN1 inhibits colony formation, cell proliferation, migration, and invasion, and induces apoptosis and G1/S arrest in esophageal cancer cells. NRN1 suppresses KYSE150 and KYSE30 cells xenografts growth in nude mice. PI3K signaling is reported to activate ATR signaling by targeting CHK1, the downstream component of ATR. By analyzing the synthetic efficiency of NVP‐BEZ235 (PI3K inhibitor) and VE‐822 (an ATR inhibitor), we found that the combination of NVP‐BEZ235 and VE‐822 increased cytotoxicity in NRN1 methylated esophageal cancer cells, as well as KYSE150 cell xenografts. In conclusion, NRN1 suppresses esophageal cancer growth both in vitro and in vivo by inhibiting PI3K‐Akt‐mTOR signaling. Methylation of NRN1 is a novel synthetic lethal marker for PI3K‐Akt‐mTOR and ATR inhibitors in human esophageal cancer. Abstract : The combination of NVP‐BEZ235 and VE‐822 increased cytotoxicity in NRN1 methylated esophageal cancer cells. Methylation of NRN1 is a novel synthetic lethal marker for PI3K‐Akt‐mTOR and ATR inhibitors in human esophageal cancer.